Utility of Earth Observation data in mapping post-disaster impact: A case of Hurricane Dorian in the Bahamas - Mohammed Ozigis; Oluropo Ogundipe; Samuel J. Valman; Jessica L. Decker Sparks; Helen McCabe; Rebekah Yore; Bethany Jackson (Remote Sensing Applications: Society and Environment, 2025)

An AI approach to operationalise global daily PlanetScope satellite imagery for river water masking - Samuel J. Valman; Doreen S. Boyd; Patrice E. Carbonneau; Matthew F. Johnson; Stephen J. Dugdale (Remote Sensing of Environment, 2024)

A possible role for river restoration enhancing biodiversity through interaction with wildfire - Brittany E. Pugh; Megan Colley; Stephen J. Dugdale; Patrick Edwards; Rebecca Flitcroft; Andrés Holz; Matthew Johnson; Michela Mariani; Mickey Means‐Brous; Kate Meyer; Kevan B. Moffett; Lisa Renan; et al. (Global Ecology and Biogeography, 2022)
Background Historically, wildfire regimes produced important landscape‐scale disturbances in many regions globally. The “pyrodiversity begets biodiversity” hypothesis suggests that wildfires that generate temporally and spatially heterogeneous mosaics of wildfire severity and post‐burn recovery enhance biodiversity at landscape scales. However, river management has often led to channel incision that disconnects rivers from their floodplains, desiccating floodplain habitats and depleting groundwater. In conjunction with predicted increases in frequency, intensity and extent of wildfires under climate change, this increases the likelihood of deep, uniform burns that reduce biodiversity. Predicted synergy of river restoration and biodiversity increase Recent focus on floodplain re‐wetting and restoration of successional floodplain habitat mosaics, developed for river management and flood prevention, could reduce wildfire intensity in restored floodplains and make the burns less uniform, increasing climate‐change resilience; an important synergy. According to theory, this would also enhance biodiversity. However, this possibility is yet to be tested empirically. We suggest potential research avenues. Illustration and future directions We illustrate the interaction between wildfire and river restoration using a restoration project in Oregon, USA. A project to reconnect the South Fork McKenzie River and its floodplain suffered a major burn (“Holiday Farm” wildfire, 2020), offering a rare opportunity to study the interaction between this type of river restoration and wildfire; specifically, the predicted increases in pyrodiversity and biodiversity. Given the importance of river and wetland ecosystems for biodiversity globally, a research priority should be to increase our understanding of potential mechanisms for a “triple win” of flood reduction, wildfire alleviation and biodiversity promotion.